SNO 2 -thick films obtained by electrophoretic deposition and their technological applications - Lustosa, Glauco M. M. M. [UNESP]; Teixeira, Guilhermina F. [UNESP]; Costa, João Paulo C. [UNESP]; Kisen, Carla Y. [UNESP]; Perazolli, Leinig A. [UNESP]; Zaghete, Maria A. [UNESP] (My University, 2017)
The study of materials prepared as films unfolds a new generation of devices paving the way towards the development of new technologies. This ongoing progress in the study of materials clearly brings relevant advantages to the fore. Among such advantages includes the possibility of developing smaller and lighter materials, which help to improve their integration with technology. Among the deposition techniques for obtaining films, the Electrophoretic Deposition (EPD) method has attracted considerable attention owing to the possibility it provides for controlling film thickness by uniform deposition in a fast and less costly manner. The EPD method has been efficient in the production of SnO 2 films with thickness controlled according to deposition time. SnO 2 is categorized as an n-type semiconductor with electrical conductivity related to excess electrons and structural defects. SnO2 band gap (around 3.6 eV) facilitates the electron excitation from the valence band (VB) to the conduction band (CB). This behavior enables the application of SnO 2 as either photocatalysts, sensors, biosensors, varistors and solar cells in addition to its use for corrosion protection. Tin dioxide (SnO 2 ) exhibits high thermal and mechanical stability besides showing electrical resistance behavior which is highly dependent on chemical composition and thermal treatment temperature. Our objective here is to explain the chemical synthesis via the Polymeric Precursor Method aimed at obtaining SnO 2 nanoparticles used for thick films deposition by EPD. The films’ characterizations show that they present a satisfactory response, rendering them suitable for application as varistors, gas sensors and photocatalysts.
Keywords: Chemical synthesis; Electrophoretic deposition; Microwave sintering; Tin dioxide